AB0282 Rheumatoid arthritis patients achieved better quality of life than systemic lupus erythematosus patients at sustained remission: the impact of disease diagnosis on health-related quality of life outcomes. (15th June 2017) - Ramos, V Pascual; Contreras-Yáñez, I; Llorente, L; Valencia-Quiñones, KR; Romero-Díaz, J
Abstract : Background: Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) impact the health related quality of life (HRQoL) of the patients. The 36 item Medical Outcome Study Short-Form survey (SF-36) assesses HRQoL and allows comparison of outcomes among different conditions. Whether remission represents similar status in terms of QoL in RA and SLE patients is unknown. In 2004 and 1999, respectively, recent-onset RA and SLE cohorts were initiated in a referral center for rheumatic diseases in México City; the SF-36 was applied beginning from enrollment. Objectives: To compare the SF-36v2 scores between patients from both cohorts who achieved for the first time sustained remission (SR) and to define the role of disease diagnosis as associated to SF-36v2 normative data in SR patients. Methods: First SR was considered when RA and SLE patients achieved at least 12 months of continuous follow-up with either SLE disease activity index 2000 update =0 or Disease Activity Score (28 joints) ≤2.4, respectively. Up to December 2015, updated data from 172 RA patients and 211 SLE patients with at least one year of follow-up were reviewed. In the SLE cohort, SF-36 was incorporated to routine assessments from 2005 onwards, meanwhile in the RA cohort it was applied since the beginning of enrollment. The SF-36v2 licensee re-scored the SF-36 used in the SLE cohort. In all the cases, Spanish versions were used and scoring was adjusted by gender and age. SF-36v2 scores were available for the totality of SR assessments. Logistic regression models were used to investigate factors associated with normative SF-36v2. Written informed consent was obtained from all patients. Results: Cohorts were integrated primarily by middle-aged females (89%), with recent-onset disease (5.3±3.2 months); at inclusion, RA patients were older and lesser educated; follow-up was longer in SLE patients (10.6±2.9 vs. 7.5±3.2 years, p≤0.001) and a higher number of them died (15% vs. 2%, p≤0.001). A higher proportion of patients achieved SR sooner in the recent-onset RA cohort than in the SLE cohort: 58% vs. 30.6% of the patients, after 30.8±23.9 vs. 59.4±37.5 months, respectively, p≤0.001. At SR, RA patients achieved better scores in 6 out of 8 SF-36v2 domains and in the physical health component summary (PHCS) compared with SLE patients; also, a greater proportion of RA patients achieved norms in five domains and in the PHCS; SLE patients achieved more frequent roles (physical and emotional) norms and scored higher mental health component summary than their counterpart. Finally, at SR RA patients had greater improvement in the majority of SF-36v2 domains and both summary components, despite having worse SF-36v2 scores at baseline evaluation. In SR patients from both cohorts, age (β: 1.06, 95% CI: 1.02–1.1, p=0.03) and SLE diagnosis (β: 9.64, 95% CI: 3.61–25.75, p≤0.001) were predictors of not achieving normative PHCS. Conclusions: RA patients who achieved SR had better HRQoL than their SLE counterparts. Age and SLE diagnosis were associated with not achieving HRQoL norms in SR patients. Disclosure of Interest: None declared